Transient thermal expansion stone cracking agent and preparation method thereof
By crosslinking silane coupling agent with starch gel and compounding phosphoric acid with perchloric acid, the prepared transient thermally expanded stone cracking agent maintains a high ignition rate under different environments, solving the problem of poor stability in the prior art and ensuring ignition reliability.
Patent Information
- Application Number
- CN202510504457.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-07-25
AI Technical Summary
The existing transient thermally expanded rock cracking agent has poor stability in high temperature and humid environments, resulting in a decrease in ignition rate and rock cracking effect.
The silane coupling agent is used to cross-link with starch gel to form a high-stability starch gel-calcium peroxide modification, and the transient thermally expanded lithotrip agent is prepared by combining phosphoric acid and perchloric acid.
It can be ignited stably and efficiently in both room temperature dry and high temperature humid environments, ensuring ignition reliability and improving the use effect in complex environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the cross - technical field of materials science and new energy. More specifically, the present invention relates to a transient thermal expansion stone - splitting agent and a preparation method thereof. Background Art
[0002] A transient thermal expansion stone - splitting agent is a new type of material for splitting stones. It uses the reaction of its own combustibles and oxides to trigger intense combustion, thereby generating a large amount of gas and heat. In a limited space, such as in a rock drill hole, the heat generated by combustion will cause the gas to expand rapidly, generating a huge pressure. When this pressure exceeds the tensile strength of the rock, the rock will crack, thus achieving the purpose of splitting the stone.
[0003] The patent with the application number 202310764306.3 discloses a method for preparing a transient thermal expansion stone - splitting agent by chemical deposition. Using water as the basic liquid, anhydrous ethanol and polyethylene glycol as dispersants, and perchloric acid, calcium peroxide, starch glue, etc. as raw materials, the transient thermal expansion stone - splitting agent is prepared by chemical deposition, solving the problems such as flameout or non - combustion during combustion caused by uneven mixing of traditional transient thermal expansion stone - splitting agents prepared by mechanical ball milling. Among them, starch glue is used to physically connect calcium peroxide with other components to form the whole stone - splitting agent. However, starch glue and calcium peroxide are prone to deterioration in high - temperature and humid environments (such as underground operations or rainy areas), resulting in a decrease in the stability of the stone - splitting agent, thereby reducing the ignition rate and stone - splitting effect of the stone - splitting agent.
[0004] Therefore, it is worthy of deep consideration how to design a new transient thermal expansion stone - splitting agent to solve the above - mentioned technical defects. Summary of the Invention
[0005] An object of the present invention is to provide a preparation method of a transient thermal expansion stone - splitting agent, including the following steps: S1. Dissolve magnesium oxide powder in a perchloric acid - phosphoric acid mixed solution to obtain a first mixture; S2. Add bituminous coal mixture, rice husk powder, coal mixture powder, catalyst, and dispersant to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain a filter residue; S4. Add a starch glue solution to a silane coupling agent solution, and stir and cross - link at 40 - 60 °C for 1 - 2 h to obtain a silane - starch glue conjugate; S5. Add calcium peroxide to the silane - starch glue conjugate, stir at room temperature for 30 - 60 min, then filter to obtain a solid product, and dry the solid product at 50 - 70 °C for 20 - 30 min to obtain a starch glue - calcium peroxide modifier.
[0006] S6. Mix the starch glue-calcium peroxide modifier evenly with the filter residue in step S3, knead, knead, granulate, and dry at 70-80 °C to obtain a transient thermal expansion rock splitting agent.
[0007] Preferably, the mass ratio of the magnesium oxide powder to the perchloric acid-phosphoric acid mixed solution is 1:2-5, and among them, the mass ratio of HClO4 to H3PO4 in the perchloric acid-phosphoric acid mixed solution is 1:0.02-3.
[0008] Preferably, the mass ratio of the magnesium oxide powder, bituminous coal mixture, rice husk powder, coal mixture powder, and catalyst is 0.3:3-5:1-2:2-4:0.1-0.3, and the catalyst is copper oxide.
[0009] Preferably, the dispersant is a mixture of anhydrous ethanol and polyethylene glycol, and the addition amounts of anhydrous ethanol and polyethylene glycol are respectively 1 / 3-1 / 5 and 1 / 100-1 / 50 of the mass of the second mixture.
[0010] Preferably, the mass ratio of potassium nitrate powder to magnesium oxide powder is 2.5-3:1.
[0011] Preferably, the solute mass of the starch glue solution is 1-2% of the mass of the second mixture, and the solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax according to a mass ratio of 50:18:1:6.5; The solvent of the starch glue solution is water, and the mass of the solvent is 10-15 times the mass of the starch glue solute.
[0012] Preferably, the mass ratio of the silane coupling agent solution to the starch glue solution is 3-5:1, and the preparation method of the silane coupling agent solution includes the following steps: Add the silane coupling agent to deionized water, add acetic acid to adjust the pH value to 4-5, and then stir at room temperature for 30-60 min. Among them, the mass ratio of the silane coupling agent to deionized water is 1:5-20, and the silane coupling agent is any one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane.
[0013] Preferably, the molar ratio of calcium peroxide to the silane coupling agent is 1:1-3.
[0014] Preferably, the bituminous coal mixture is a mixture of anthracite and semi-bituminous coal with a mass ratio of 2:8-4:6; The coal mixture powder is a mixture of coal gangue and coal slime with a mass ratio of 6:4-8:2.
[0015] Provide a transient thermal expansion rock splitting agent prepared by the described preparation method.
[0016] The present invention has at least the following beneficial effects: First, the present invention cross-links through a silane coupling agent and starch glue to form a cross-linked structure, and at the same time reacts with calcium peroxide to generate a starch glue-calcium peroxide modifier with high stability. After granulating the modifier with filter residue, the obtained transient thermal expansion stone breaker can be stably and efficiently ignited in a conventional normal temperature and dry environment or a harsh high temperature and humid environment, ensuring the ignition reliability in actual use.
[0017] Second, the present invention effectively improves the stability of the transient thermal expansion stone breaker by compounding phosphoric acid and perchloric acid, and still has a high ignition rate in a high humidity environment.
[0018] Other advantages, objectives and features of the present invention will be partially reflected by the following description, and partially will be understood by those skilled in the art through the research and practice of the present invention. Detailed implementation manners
[0019] The following further elaborates on the present invention in conjunction with embodiments, so that those skilled in the art can implement it with reference to the text of the specification.
[0020] It should be noted that the experimental methods described in the following implementation schemes are all conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0021] <Example 1> A preparation method of a transient thermal expansion stone breaker includes the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 0.6 kg of a perchloric acid-phosphoric acid mixed solution, wherein the mass ratio of HClO4 to H3PO4 in the perchloric acid-phosphoric acid mixed solution is 1:0.02 to obtain a first mixture; S2. Add 3 kg of a bituminous coal mixture (the mass ratio of anthracite to semi-bituminous coal is 2:8), 1 kg of rice husk powder, 6 kg of a coal mixture powder (the mass ratio of coal gangue to coal slime is 6:4), 0.1 kg of a catalyst (copper oxide), and a dispersant (the mass of anhydrous ethanol is 1 / 5 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 50 of the mass of the second mixture) to the first mixture, and stir evenly at normal temperature to obtain a second mixture; S3. Add 0.75 kg of potassium nitrate powder to the second mixture, stir evenly at normal temperature, and filter to obtain filter residue; S4. Mix the silane coupling agent solution and the starch glue solution at a mass ratio of 3:1, and stir and crosslink them at 40 °C for 2 h to obtain a silane-starch glue conjugate. Among them, the solute mass of the starch glue solution is 1% of the mass of the second mixture. The solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax at a mass ratio of 50:18:1:6.5, and the solvent (water) mass is 10 times the mass of the starch glue solute. The preparation method of the silane coupling agent solution includes: Mix γ-aminopropyltriethoxysilane and deionized water at a mass ratio of 1:20, adjust the pH value to 4 with acetic acid, and stir at room temperature for 30 min; S5. Add calcium peroxide (the molar ratio of calcium peroxide to the silane coupling agent is 1:3) to the silane-starch glue conjugate, stir at room temperature for 30 min, then filter to obtain a solid product, and dry the solid product at 50 °C for 30 min to obtain a starch glue-calcium peroxide modifier; S6. Mix the starch glue-calcium peroxide modifier with the filter residue in step S3 evenly, knead, roll, granulate, and dry at 70 °C to obtain a transient thermal expansion stone cracker.
[0022] <Example 2> A preparation method of a transient thermal expansion stone cracker, comprising the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 1.05 kg of a perchloric acid-phosphoric acid mixed solution, wherein the mass ratio of HClO4 to H3PO4 in the perchloric acid-phosphoric acid mixed solution is 1:1.51 to obtain a first mixture; S2. Add 4 kg of a bituminous coal mixture (the mass ratio of anthracite and semi-bituminous coal is 3:7), 1.5 kg of rice husk powder, 9 kg of a coal mixture powder (the mass ratio of coal gangue and coal slime is 7:3), 0.2 kg of a catalyst (copper oxide), and a dispersant (the mass of anhydrous ethanol is 1 / 4 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 75 of the mass of the second mixture) to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add 0.825 kg of potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain a filter residue; S4. Mix the silane coupling agent solution and the starch glue solution at a mass ratio of 4:1, and stir and crosslink them at 50 °C for 1.5 h to obtain a silane-starch glue conjugate. Among them, the solute mass of the starch glue solution is 1.5% of the mass of the second mixture. The solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax at a mass ratio of 50:18:1:6.5, and the solvent (water) mass is 12.5 times the mass of the starch glue solute. The preparation method of the silane coupling agent solution includes: Mix vinyltriethoxysilane and deionized water at a mass ratio of 1:12.5, adjust the pH value to 4 with acetic acid, and stir at room temperature for 45 min; S5. Add calcium peroxide (the molar ratio of calcium peroxide to silane coupling agent is 1:2) to the silane-starch glue conjugate, stir at room temperature for 45 min, then filter to obtain a solid product, and dry the solid product at 60 °C for 25 min to obtain a starch glue-calcium peroxide modifier; Step S6: Mix the starch glue-calcium peroxide modifier and the filter residue in step S3 evenly, knead, pelletize, and dry at 70 °C to obtain a transient thermal expansion stone breaker.
[0023] <Example 3> A preparation method of a transient thermal expansion stone breaker, comprising the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 1.5 kg of a perchloric acid-phosphoric acid mixed solution, wherein the mass ratio of HClO4 to H3PO4 in the perchloric acid-phosphoric acid mixed solution is 1:3 to obtain a first mixture; S2. Add 5 kg of bituminous coal mixture (the mass ratio of anthracite to semi-bituminous coal is 4:6), 2 kg of rice husk powder, 12 kg of coal mixture powder (the mass ratio of coal gangue to coal slime is 8:2), 0.3 kg of catalyst (copper oxide), and dispersants (the mass of absolute ethanol is 1 / 3 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 100 of the mass of the second mixture) to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add 0.9 kg of potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain a filter residue; S4. Mix the silane coupling agent solution and the starch glue solution at a mass ratio of 5:1, stir and crosslink at 60 °C for 1 h to obtain a silane-starch glue conjugate, wherein the solute mass of the starch glue solution is 2% of the mass of the second mixture, and the solute of the starch glue solution is mixed according to the mass ratio of 50:18:1:6.5 of corn starch, sodium hydroxide, potassium pyroantimonate, and borax, and the mass of the solvent (water) is 15 times the mass of the starch glue solute. The preparation method of the silane coupling agent solution includes: Mix γ-glycidoxypropyltrimethoxysilane and deionized water at a mass ratio of 1:5, adjust the pH value to 4 with acetic acid, and stir at room temperature for 60 min; S5. Add calcium peroxide (the molar ratio of calcium peroxide to silane coupling agent is 1:1) to the silane-starch glue conjugate, stir at room temperature for 60 min, then filter to obtain a solid product, and dry the solid product at 70 °C for 20 min to obtain a starch glue-calcium peroxide modifier; S6. Mix the starch glue-calcium peroxide modifier evenly with the filter residue in step S3, knead, knead, granulate, and dry at 70 °C to obtain the transient thermal expansion stone cracker.
[0024] <Comparative Example 1> The preparation method of the transient thermal expansion stone cracker is different from that of Example 1 in that the starch glue, calcium peroxide and the filter residue are directly granulated to obtain the transient thermal expansion stone cracker, and γ-glycidyl ether oxypropyltrimethoxysilane is not added.
[0025] The above preparation method of the transient thermal expansion stone cracker includes the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 0.6 kg of perchloric acid-phosphoric acid mixed solution, wherein the mass ratio of HClO4 to H3PO4 in the perchloric acid-phosphoric acid mixed solution is 1:0.02 to obtain the first mixture; S2. Add 3 kg of bituminous coal mixture (the mass ratio of anthracite and semi-bituminous coal is 2:8), 1 kg of rice husk powder, 6 kg of coal mixture powder (the mass ratio of coal gangue and coal slime is 6:4), 0.1 kg of catalyst (copper oxide), and dispersant (the mass of absolute ethanol is 1 / 5 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 50 of the mass of the second mixture) to the first mixture, and stir evenly at room temperature to obtain the second mixture; S3. Add 0.75 kg of potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain the filter residue; S4. Mix the starch glue solution, 2 kg of calcium peroxide with the filter residue in step S3 evenly, knead, knead, granulate, and dry at 70 °C to obtain the transient thermal expansion stone cracker, wherein the solute mass of the starch glue solution is 1% of the mass of the second mixture, and the solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax according to a mass ratio of 50:18:1:6.5, and the mass of the solvent (water) is 10 times the mass of the starch glue solute.
[0026] <Comparative Example 2> The preparation method of the transient thermal expansion stone cracker is different from that of Example 1 in that the starch glue, calcium peroxide, and γ-glycidyl ether oxypropyltrimethoxysilane are simply physically mixed without including steps such as crosslinking.
[0027] The above preparation method of the transient thermal expansion stone cracker includes the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 0.6 kg of perchloric acid-phosphoric acid mixed solution, wherein the mass ratio of HClO4 to H3PO4 in the perchloric acid-phosphoric acid mixed solution is 1:0.02 to obtain the first mixture; S2. Add 3 kg of bituminous coal mixture (the mass ratio of anthracite to semi-bituminous coal is 2:8), 1 kg of rice husk powder, 6 kg of coal mixture powder (the mass ratio of coal gangue to slime is 6:4), 0.1 kg of catalyst (copper oxide), and dispersants (the mass of anhydrous ethanol is 1 / 5 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 50 of the mass of the second mixture) to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add 0.75 kg of potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain a filter residue; S4. Mix and stir γ-aminopropyltriethoxysilane, starch glue solution, and 2 kg of calcium peroxide (the molar ratio of calcium peroxide to γ-aminopropyltriethoxysilane is 1:3) (at room temperature) for 10 min to obtain a starch glue-silane-calcium peroxide mixture. Among them, the solute mass of the starch glue solution is 1% of the mass of the second mixture, and the solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax in a mass ratio of 50:18:1:6.5, and the solvent (water) mass is 10 times the mass of the starch glue solute; S5. Mix the solid obtained by filtering the starch glue-silane-calcium peroxide mixture with the filter residue in step S3 evenly, knead, granulate, and dry at 70 °C to obtain a transient thermal expansion stone cracker.
[0028] <Comparative Example 3> The preparation method of the transient thermal expansion stone cracker is different from that of Example 1 in that magnesium oxide powder is dissolved in perchloric acid solution (mass concentration of 68%) and does not include phosphoric acid.
[0029] The above preparation method of the transient thermal expansion stone cracker includes the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 0.6 kg of perchloric acid solution (mass fraction of 68%) to obtain a first mixture; S2. Add 3 kg of bituminous coal mixture (the mass ratio of anthracite to semi-bituminous coal is 2:8), 1 kg of rice husk powder, 6 kg of coal mixture powder (the mass ratio of coal gangue to slime is 6:4), 0.1 kg of catalyst (copper oxide), and dispersants (the mass of anhydrous ethanol is 1 / 5 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 50 of the mass of the second mixture) to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add 0.75 kg of potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain a filter residue; S4. Mix the silane coupling agent solution and the starch glue solution at a mass ratio of 3:1, stir and crosslink at 40 °C for 2 h to obtain a silane-starch glue conjugate. Among them, the solute mass of the starch glue solution is 1% of the mass of the second mixture. The solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax at a mass ratio of 50:18:1:6.5. The mass of the solvent (water) is 10 times the mass of the starch glue solute. The preparation method of the silane coupling agent solution includes: Mix γ-aminopropyltriethoxysilane and deionized water at a mass ratio of 1:20, adjust the pH value to 4 with acetic acid, and stir at room temperature for 30 min; S5. Add calcium peroxide (the molar ratio of calcium peroxide to the silane coupling agent is 1:3) to the silane-starch glue conjugate, stir at room temperature for 30 min, then filter to obtain a solid product, and dry the solid product at 50 °C for 30 min to obtain a starch glue-calcium peroxide modifier; S6. Mix the starch glue-calcium peroxide modifier and the filter residue in step S3 evenly, knead, knead, granulate, and dry at 70 °C to obtain a transient thermal expansion stone cracker.
[0030] <Comparative Example 4> The preparation method of the transient thermal expansion stone cracker is different from that of Example 1 in that the starch glue, calcium peroxide and the filter residue are directly granulated to obtain the transient thermal expansion stone cracker, and γ-glycidoxypropyltrimethoxysilane is not added.
[0031] The above preparation method of the transient thermal expansion stone cracker includes the following steps: S1. Dissolve 0.3 kg of magnesium oxide powder in 0.6 kg of perchloric acid solution (mass fraction of 68%) to obtain a first mixture; S2. Add 3 kg of bituminous coal mixture (the mass ratio of anthracite and semi-bituminous coal is 2:8), 1 kg of rice husk powder, 6 kg of coal mixture powder (the mass ratio of coal gangue and coal slime is 6:4), 0.1 kg of catalyst (copper oxide), and dispersant (the mass of absolute ethanol is 1 / 5 of the mass of the second mixture, and the mass of polyethylene glycol is 1 / 50 of the mass of the second mixture) to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add 0.75 kg of potassium nitrate powder to the second mixture, stir evenly at room temperature, filter, and obtain a filter residue; S4. Mix the starch glue solution, 2 kg of calcium peroxide, and the filter residue from step S3 evenly, knead, knead, granulate, and dry at 70 °C to obtain a transient thermal expansion stone cracker. Among them, the solute mass of the starch glue solution is 1% of the mass of the second mixture. The solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax in a mass ratio of 50:18:1:6.5, and the mass of the solvent (water) is 10 times the mass of the starch glue solute.
[0032] The starch glue-calcium peroxide modifiers prepared in Examples 1 to 3 and Comparative Example 3 were analyzed by infrared spectroscopy, and it was found that: An absorption peak appears near 1100 cm⁻¹, indicating the formation of silicon-oxygen bonds (Si-O-Si); An absorption peak appears near 930 cm⁻¹, indicating the presence of silanol groups (Si-OH); An absorption peak appears near 870 cm⁻¹, indicating the presence of peroxy bonds (O-O); An absorption peak appears near 530 cm⁻¹, indicating the presence of calcium-oxygen bonds (Ca-O) An absorption peak appears near 1180 cm⁻¹, indicating the ring-opening reaction of epoxy groups (C-O-C); A broad absorption peak appears near 3300 cm⁻¹, indicating the presence of hydroxyl groups (O-H); Strong absorption peaks appear near 2850 cm⁻¹, corresponding to the C-H stretching vibration of alkyl groups.
[0033] The above data show that the starch glue is fully crosslinked with γ-glycidoxypropyltrimethoxysilane to form a crosslinked structure, and calcium peroxide forms a certain complex with γ-glycidoxypropyltrimethoxysilane or starch glue.
[0034] <Combustion test> The dry transient thermal expansion stone crackers prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were evenly divided into two groups: Group A was stored in a normal temperature and dry environment, and Group B was placed in a high temperature and humid environment simulation box (temperature 60 °C, humidity 80%). After 60 days of placement in both groups, it was found that there was no obvious change in the appearance of Group B of Examples 1 to 3, while the appearance of Group B of Comparative Examples 1 to 4 showed caking phenomena to varying degrees, and the particle shape also changed to varying degrees.
[0035] The ignition rate tests were carried out on each group. Among them, the steps of the ignition rate test included: preparing 100 rock drill holes respectively, filling the rock splitting agent according to the standard operation process, igniting with a special ignition device on the 10th day, 30th day, and 60th day of storage, counting the number of drill holes with successful ignition, calculating the ignition rate, repeating the experiment 3 times, and taking the average value; there was almost no difference in the ignition rate of Group A on the 10th day, 30th day, and 60th day of storage, so the ignition rate on the 60th day was recorded in the following table. The results of the ignition rate test are shown in Table 1 below: Table 1 Ignition rates of each group after storage in different environments According to the data in Table 1, Examples 1-3 showed relatively high ignition rates in both the normal temperature and dry environment and the high temperature and humid environment, which were 97-98% and 96-97% respectively. This indicates that the transient thermal expansion rock splitting agent prepared according to the method of the present invention can be stably and efficiently ignited whether it is stored in a conventional normal temperature and dry environment or a harsh high temperature and humid environment, ensuring the ignition reliability in actual use; However, there were obvious differences in the ignition rates of Comparative Examples 1-4 in the normal temperature and dry environment and the high temperature and humid environment. In the normal temperature and dry Group A environment, the ignition rate was acceptable, maintaining at 97-98%. However, after being stored in the high temperature and humid Group B environment for 10 days and 30 days, the ignition rate decreased sharply. For example, in Comparative Example 1, it decreased from 98% to 74% and then to 67%, in Comparative Example 2, it decreased from 97% to 72% and then to 64%, in Comparative Example 4, it decreased from 97% to 71% and then to 59%, and in Comparative Example 3, although the decrease amplitude was relatively small, it also decreased from 97% to 78% and then to 68%. This shows that not using γ-glycidoxypropyltrimethoxysilane to react with starch glue and calcium peroxide, and not adding phosphoric acid will result in poor tolerance of the rock splitting agent to the high temperature and humid environment, greatly affecting its use effect in actual complex environments; the ignition rates of Comparative Examples 1-4 after being stored in the high temperature and humid Group B environment for 30 days and 60 days were not much different, indicating that when the transient thermal expansion rock splitting agent prepared in Comparative Examples 1-4 was stored in the high temperature and humid environment for 30 days, it was almost completely deteriorated and no longer had a great impact on the ignition rate.
[0036] By comprehensively comparing Examples 1-3 and Comparative Examples 1-4, the ignition rate of the transient thermal expansion rock splitting agent prepared by the present invention fluctuates very little under different environmental conditions, and its stability is significantly higher than that of Comparative Examples 1-4. This shows that using γ-glycidoxypropyltrimethoxysilane to react with starch glue and calcium peroxide, and combining the compounding of phosphoric acid and perchloric acid can enable the rock splitting agent to maintain good physical and chemical properties in various environments, ensuring that the ignition performance is not interfered by environmental factors, providing a reliable guarantee for engineering operations such as rock mining.
[0037] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those skilled in the art, additional modifications can be easily achieved. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. Preparation method of transient thermal expansion rock splitting agent, characterized in that, It includes the following steps: S1. Dissolve magnesium oxide powder in a perchloric acid - phosphoric acid mixed solution to obtain a first mixture; S2. Add bituminous coal mixture, rice husk powder, coal mixture powder, catalyst, and dispersant to the first mixture, and stir evenly at room temperature to obtain a second mixture; S3. Add potassium nitrate powder to the second mixture, stir evenly at room temperature, and filter to obtain a filter residue; S4. Add a starch glue solution to a silane coupling agent solution, stir and crosslink at 40 - 60 °C for 1 - 2 h to obtain a silane - starch glue conjugate; S5. Add calcium peroxide to the silane - starch glue conjugate, stir at room temperature for 30 - 60 min, then filter to obtain a solid product, and dry the solid product at 50 - 70 °C for 20 - 30 min to obtain a starch glue - calcium peroxide modifier; S6. Mix the starch glue - calcium peroxide modifier evenly with the filter residue in step S3, knead, pelletize, and dry at 70 - 80 °C to obtain a transient thermal expansion stone - splitting agent.
2. The preparation method of the transient thermal expansion rock splitting agent according to claim 1, characterized in that, The mass ratio of magnesium oxide powder to the perchloric acid - phosphoric acid mixed solution is 1:2 - 5, wherein the mass ratio of HClO4 to H3PO4 in the perchloric acid - phosphoric acid mixed solution is 1:0.02 - 3.
3. The preparation method of the transient thermal expansion rock splitting agent according to claim 2, characterized in that, The mass ratio of magnesium oxide powder, bituminous coal mixture, rice husk powder, coal mixture powder, and catalyst is 0.3:3 - 5:1 - 2:2 - 4:0.1 - 0.3, and the catalyst is copper oxide.
4. The preparation method of the transient thermal expansion rock splitting agent according to claim 1, characterized in that, The dispersant is a mixture of absolute ethanol and polyethylene glycol, and the addition amounts of absolute ethanol and polyethylene glycol are 1 / 3 - 1 / 5 and 1 / 100 - 1 / 50 of the mass of the second mixture respectively.
5. The preparation method of the transient thermal expansion stone cracker according to claim 2, characterized in that, The mass ratio of potassium nitrate powder to magnesium oxide powder is 2.5 - 3:
1.
6. The preparation method of the transient thermal expansion rock splitting agent according to claim 1, characterized in that, The solute mass of the starch glue solution is 1 - 2% of the mass of the second mixture, and the solute of the starch glue solution is mixed with corn starch, sodium hydroxide, potassium pyroantimonate, and borax in a mass ratio of 50:18:1:6.5; The solvent of the starch glue solution is water, and the mass of the solvent is 10 - 15 times the mass of the starch glue solute.
7. The preparation method of the transient thermal expansion stone splitting agent according to claim 6, characterized in that, The mass ratio of the silane coupling agent solution to the starch glue solution is 3 - 5:1, and the preparation method of the silane coupling agent solution includes the following steps: Add a silane coupling agent to deionized water, adjust the pH value to 4 - 5 with acetic acid, and then stir at room temperature for 30 - 60 min. Among them, the mass ratio of the silane coupling agent to deionized water is 1:5 - 20, and the silane coupling agent is any one of γ - aminopropyltriethoxysilane, vinyltriethoxysilane, and γ - glycidyletheroxypropyltrimethoxysilane.
8. The preparation method of the transient thermal expansion stone-cracking agent according to claim 1, characterized in that, The molar ratio of calcium peroxide to the silane coupling agent is 1:1 - 3.
9. The preparation method of the transient thermal expansion stone-cracking agent according to claim 1, characterized in that, The bituminous coal mixture is a mixture of anthracite and semi - bituminous coal with a mass ratio of 2:8 - 4:6; The coal mixture powder is a mixture of coal gangue and coal slime with a mass ratio of 6:4 - 8:
2.
10. A transient thermal expansion stone - splitting agent prepared by the preparation method according to any one of claims 1 - 9.
Citation Information
Patent Citations
Cation modified starch, preparation method and applications thereof
CN104119455A
Starch adhesive and preparation method thereof
CN105400448A
Method for preparing expandable graphite
CN106698413A
Method for preparing transient thermal expansion stone cracking agent by chemical deposition method
CN116813438A
Self-generating foamed drilling fluids
US20040110643A1